(untitled) (Educação e Pesquisa, 2021)
The purpose of this article is to propose a new way of understanding teaching based on the term teaching logic, in other words, a principle of justice comprising teaching knowledge and mobilised by teachers in their professional activities. The drawing up of this concept was inspired by pragmatic sociology and by the following questions: what would the action logics be that guide the conduct of teachers? Are the same action logics deployed by teachers in different sociocultural contexts? Would it be possible to find similarities between the principles of justice of French and Brazilian professionals? To answer these questions, field observations were carried out and 36 Brazilian and French teachers were invited to describe professional situations in semi-structured interviews. The analysis of scenarios linked to teachers’ real activities reveals that although there is a plurality of logics, there is a tendency to use a civic logic in France and a liberal logic in Brazil. The discussion of this result demonstrates that action logics are limited to privileged justice criteria in national contexts. Nevertheless, it was possible to conclude that, even in different sociocultural settings, there is professional knowledge shared by teachers in both countries, which are translated into principles of justice and comprise a teaching action logic.